General provisions of medical physical training in diseases of the urinary tract in the postoperative period. - Zaytsev V.P; Manucharyan S.V; Hagner-Derengowska M.; Iermakov S.S (Kharkov National Pedagogical University, 2011)
The published sources and personal experience on the issue of recovery after surgery for diseases of the urinary system are considered. Found that some specialists in medical physical culture does not always adhere to general principles of physiotherapy sessions. We propose methodological approaches to the treatment of physical culture, has been found that in stationary conditions must be specific pathology and severity of illness. It is established that free motoring mode, you can use all the means of medical physical culture. It is also recommended by the medical-pedagogical control.